(untitled) (Research, Society and Development, 2026)
This study aims to analyze the importance of responsibility and adequate disposal of Lubricant Oil Used or Contaminated (LOUC), highlighting its impacts on public health and the environment. Classified as hazardous waste due to its toxic load and the presence of heavy metals, LOUC requires rigorous management, as improper disposal degrades natural resources and compromises human integrity. The methodology consisted of a literature review and documentary analysis based on the National Solid Waste Policy (PNRS) and the National Environment Council (CONAMA) Resolution No. 362/2005. The results indicate that the effectiveness of the legislation rests on the principle of shared responsibility, which links producers, retailers, and consumers in a cycle of mutual obligations. It is concluded that re-refining is established as the safest and most efficient disposal method, converting a toxic environmental liability into a renewable economic asset, aligned with the precepts of circular economy, global sustainability, and zero waste.